From a static to a dynamic perspective in handball match analysis: a systematic review - Prieto, J.; Gomez, M. A.; Sampaio, J. (The Open Sports Sciences Journal, 2015)
The aim of this study was to perform a systematic review of the scientific literature on handball match analysis and to identify potential research areas for future work. Data were collected from Web of Science, MEDLINE, SPORTDiscus, Scopus, EBSCO, and ProQuest databases. The initial search found 148 journal articles. Only the papers focused on handball match analysis regarding tactical and technical aspects were considered, for a final list of 25 publications. The complexity approach under which each considered publication was conducted was taken into account (i.e., static vs. dynamic). Therein, authors, main analysis, number of performance indicators under study, considered situational variables, statistics and/or analysis methods, type of competition, number of matches, and sex of participants were distinguished for classification purposes. Research on handball match analysis has evolved over the years, mainly due to the great technological advances. Studies conducted under the classical static complexity approach are the most extended. Studies performed under the relatively new dynamic complexity approach are growing. The present review identified the following main guidelines for future work on handball match analysis: conducting more studies focused on the defensive profile; analyzing handball national leagues and international club competitions; performing more studies in female handball; including game situational variables into the analysis (i.e., game type, match status, game location, quality of opposition, game period); incorporating critical events of the game into the analysis (e.g., team timeouts, exclusions); and, conducting further research from the promising dynamic complexity perspective.